Risk factors for cervical cancer among women reporting government tertiary care hospitals in Chennai, Tamil Nadu, Southern India: a cross-sectional study - Sundar, Jasmine S.; Srijayanth, Parameswari; Karthikeyan, P. R.; A. S., Hemapriya; S., Valarmathi; S., Kalpana; A., Arul Paul; Narayanasamy; G., Srinivas (International Journal of Research in Medical Sciences, 2024)
Background: Cervical cancer is widely recognized as a disease characterized by significant disparities, with marked differences in both incidence and mortality rates observed between low and middle-income countries (LMICs) and high-income countries. In India, the disease poses a substantial burden, leading to one death every 8 minutes. India’s contribution to global cervical cancer statistics is substantial, with 21% of new cases and 23% of deaths worldwide, surpassing previously leading nations like China. Within Tamil Nadu, it ranks as the second most prevalent cancer among women. This study seeks to comprehensively explore these disparities and identify associated risk factors among women undergoing treatment for cervical cancer at tertiary hospitals in Chennai. Methods: Participants (n=41) were recruited from October 2021 to May 2022 from five specialized oncology centers. Data on socio-demographic characteristics and medical history, were collected through face-to-face interviews. Results: The study participants had a mean age of 54±8.26 years, with a majority from Chennai (44%) and Northern Tamil Nadu (36.5%). Common socio-demographic features included low educational attainment (46% with no formal education), rural residence (56%), and modest income levels. Significant risk factors identified included multiparity (Crude’s OR 33.7), family history of cancer (Crude’s OR 22.5), and advancing age. Conclusions: Cervical carcinoma presents a substantial health burden among women in Chennai. This study identifies critical socio-demographic factors, including age, family history, and parity, as significant contributors to cervical cancer risk. The findings underscore the necessity for targeted public health interventions to enhance awareness and implement effective preventive strategies.